Value Patterns in Four Dimensions among the Indigenous Sami Population in Norway: A Population-Based Survey - Lenert Hansen, Ketil; Høgmo, Asle; Lund, Eiliv (Journal of Northern Studies, 2017)
Background: This is a population-based study that explores and describes a set of personal values in indigenous Sami and non-Sami adults in Norway. Norway ratified the ILO convention no. 169 concerning indigenous and tribal peoples in independent countries in 1990. In accordance with the convention the integrity of the indigenous culture and values shall be respected. Our aim is to describe and explore value patterns among Sami and Norwegian populations. Method: Cross-sectional questionnaire. From 24 local authorities, a total of 12,623 subjects between the ages of 36 and 79 were included in the analysis. The survey instrument consisted of a 19-item questionnaire of personal values and the analysis was based on responses from 10,268 ethnic Norwegian (just 6 questions were asked to them) and 2,355 Sami participants (1,531 Sami and 824 mixed Sami/ethnic Norwegian participants). Results: From the 19 values, Sami respondents held the following five personal values in the highest regard: being in touch with nature; harnessing nature through fishing, hunting and berry-picking; preserving ancestral and family traditions; preserving traditional Sami industries and preserving and developing the Sami language. On the other hand, Sami respondents’ least important values included modern Sami art and the Sami Parliament (Sametinget). The ethnic Norwegians also held being in touch with nature as a very important value. Sami reported significantly higher scores for experience of ethnic discrimination and fear of losing their work/trade than ethnic Norwegians. The last 13 questions were just asked to Sami and mixed-Sami respondents. According to those questions four dimensions associated with personal values were identified among the indigenous Sami population: “Traditional Sami Values,” “Modern Sami Values,” “Contact with Nature” and “Feeling of Marginalisation.” Traditional and modern Sami values were both characterised by significantly higher scores among females, the lowest age bracket and those who considered themselves Sami. Within the Traditional Sami Values dimension, higher scores were also recorded in participants who were married or cohabiting, living in majority Sami areas, satisfied with “way of life” and members of the Læstadian Church. The Modern Sami Values dimension showed higher scores among participants with high household incomes. The Contact with Nature dimension had significantly higher proportions of Sami, married or cohabitants, and participants content with their way of life; age, geographical area and household income were found to be insignificant variables within this dimension. Feeling of Marginalisation was characterised by significantly greater proportions of males, individuals of working age, residence in Norwegian-dominated areas, self-perceived Sami ethnicity, low household income, poorer self-reported health and dissatisfaction with way of life. Conclusion: Four distinct value patterns and relationships to well-being and self-reported health were identified in the indigenous Sami population. The four dimensions reflect important aspects of present-day Sami society.